Peran Orang Tua terhadap Pembentukan Karakter Disiplin Belajar Anak - Sulaiman Sulaiman; Nurmasyitah Nurmasyitah; M.Hussin Affan; Khalisah Khalisah (Universitas Syiah Kuala, 2022)
The Role of Parents in Character Building Children's discipline is very large and has an important role. Education is a shared responsibility, namely family, community, and school. The family is the first educational institution for children. Parents take an important role in shaping children, including shaping the character of discipline. Parents have an important role in instilling attitudes, talents, and character in children. Cooperation between parents is very influential, a father who has the skills to lead and educate must be able to teach these skills to the mother where the mother is the one who spends the most time with the child even when the child is still in the womb. So that parents can provide adequate learning and love to their children. Parents have a responsibility to shape the character of their children. One of the characters taught in the family environment is discipline.Keywords: Parents, Discipline character of children.